Edukasi Pemanfaatan Limbah Kulit Pisang Sebagai Pupuk Organik Cair Di Kampung Depet Indah - Ramidah Sihombing; Amru Hanif; Nurdiana Putri; Vikky Eliswan Ahmad; Pardila Pardila; Ika Putri Nabila; Sofiyanurriyanti Sofiyanurriyanti (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
Kampung Depet Indah is one of the villages in the Celala District, Central Aceh District. Kampung Depet Indah is located in an area that is remote in the District of Celala with its vast natural potential with agricultural land and plantations. Based on the results of surveys conducted on several farms and plantations, there are still many farmers who on average use chemical fertilizers as a source of additional or substitute nutrients needed by plants to support growth. One of the work programs being carried out is the manufacture of liquid organic fertilizer (POC) from banana peel waste, where POC itself is a liquid organic fertilizer that can be used by farmers as a provider of nutrients for plants and crops. The implementation of making POC up to the socialization stage to the community consists of several stages which include: (1) Preparation of tools and materials (2) Making POC as a sample (3) Making POC posters (4) Socializing POC to the community (5) Question and answer session.